(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes some scientific and theoretical views and studies of domestic scientists on literary continuity and the mechanisms of its action. The question of the role of tradition, improvement (progress) and innovation (innovation) in literary continuity and its continuity, the role of talent and creative power of a creative person in this process in ensuring continuity in fiction was also discussed.